SOCIAL RESPONSIBILITY OF CONSUMER SERVICES ENTITIES: FEATURES AND IMPLEMENTATION PRIORITIES (Development Service Industry Management, 2025)
The article focuses on the issues of forming and implementing a socially responsible policy by business entities. The specifics and relevance of planning and implementing socially oriented measures by enterprises operating in the field of consumer services are separately emphasized. The purpose of the study is to identify the features, as well as substantiation of priorities for implementing socially responsible behavior of consumer service entities. The study highlights transformational shifts in the priorities and directions for implementing socially responsible policy of consumer service enterprises in Ukraine under martial law. The features of socially responsible behavior of subjects in the sphere of consumer services are revealed. In particular, these include a high level of responsibility in ensuring employment of the population, including socially vulnerable categories of the population, demobilized and war veterans, and meeting the needs of the population in consumer services, ensuring inclusiveness in terms of the population's accessibility to consumer services, development of the infrastructure of territories and communities, etc. Priorities have been identified for the formation and implementation of socially responsible behavior of subjects in the consumer services sector, including improving responsibility to society, to their own personnel, to business partners, and to the territory of operation. The practical significance of the research results lies in the implementation of measures aimed at increasing the social efficiency of subjects in the sphere of consumer services. The scientific novelty of the research results lies in the further development of methodological and applied principles and provisions for managing the social responsibility of subjects in the sphere of consumer services.
Keywords: social responsibility; socially responsible policy; subjects of the consumer services sector; features; implementation priorities; consumer market; social management